Clinical features, therapeutic requirements and evolution of patients with Crohn's disease and upper gastrointestinal involvement (CROHNEX study). Issue 8 (18th August 2021) - Sainz, Empar; Zabana, Yamile; Miguel, Isabel; Fernández‐Clotet, Agnès; Beltrán, Belén; Núñez, Laura; García, María José; Martín‐Arranz, María Dolores; Iglesias, Eva; Cañete, Fiorella; Gutiérrez, Ana; Piqueras, Marta; et al.
Summary: Background: Crohn's disease (CD) with upper gastrointestinal involvement (UGI) may have a more aggressive and refractory course. However, evidence on this phenotype of patients is scarce. Aims: To identify the clinical characteristics, therapeutic requirements and complications associated with UGI in CD Methods: Nationwide study of cases (UGI, UGI plus ileal/ileocolonic involvement) paired with controls (ileal/ileocolonic involvement) from the ENEIDA registry. Cases were matched to 2 controls by year of diagnosis ± 2.5 years. Patients with exclusive/predominant colonic location or complex perianal fistula were excluded. Results: Of 24 738 patients with CD in the ENEIDA registry, we identified 4058 with UGI (16% of the total CD cohort). Finally, 854 cases and 1708 controls were included. Cases were independently associated to extensive involvement (OR 2.7 [2.2‐3.3], P  < 0.0001), strictures [OR 1.8 (1.5‐2.2), P  < 0.0001], chronic iron deficiency anaemia [OR 2.2 (1.3‐3.2), P  < 0.001] and use of second‐line biologics [OR 1.7 (1.1‐2.6), P  = 0.021]. The median stricture‐free time was 14 years (95% CI, 12‐16) for cases vs 21 years (95% CI, 19‐23) for controls ( P  < 0.0001). Cases with isolated UGI compared to UGI plus ileal/ileocolonic more frequently had localised disease [OR 0.5(0.3‐0.8), P  = 0.003] and underwent more endoscopic stricture dilations [OR 2.7(1.3‐5.4), P  = 0.006]. Conclusions: The largest cohort of patients with CD and UGI provides information on the natural history of this particular phenotype. Increased awareness of the clinical picture and therapeutic requirements of these patients could lead to earlier diagnosis and treatment of upper gastrointestinal lesions, preventing the structural damage frequently seen in these patients at diagnosis and during follow‐up. Abstract : Clinical features, therapeutic requirements and evolution of patients with Crohn's disease and upper gastrointestinal involvement (CROHNEX study)Study population: Cases: patients with Crohn'sdisease and upper gastrointestinal involvement (n = 854).Controls: patients with Crohn's disease and ileal/ilecocolonic involvement (n = 1708). Patients were identified from the ENEIDA registry (Spanish cohort of patients with inflammatory bowel disease). Cases were matched to 2 controls by year of diagnosis ± 2.5 years. Patients with exclusive/predominant colonic location and those with complex perianal fistula were excluded. Results: Cases were more likely to have: Extensive involvement (OR 2.7 [2.2‐3.3], P  < 0.0001). Strictures (OR 1.8 [1.5‐2.2], P  < 0.0001). Chronic iron deficiency anaemia (OR 2.2 [1.3‐3.2], P  < 0.001). Use of second‐line biologics (OR 1.7 [1.12.6], P  = 0.021). The median stricture‐free time was 14 years (95% CI, 12‐16) for cases vs 21 years (95% CI, 19‐23) for controls ( P  < 0.0001).